Establishment of Health Insurance Scheme for Informal Sector Populace in Ogun State Of Nigeria: A Mixed Methodology Approach - Akinremi, Amos Oluwasayo; Coker, Marcellina Oluwatomi; Dosunmu, Afolabi Oladimeji; Adeniregun, Adedapo Olugbenga; Oluwole, Adebayo Amos; Amusa, Abiodun Richard; Edun, Folarin Opeyemi; Sennuga, Atinuke Yetunde; Gaibwedsa, Obed (British Journal of Healthcare and Medical Research, 2022)
This study evaluated the perception of informal sector populace towards the proposed state health insurance (SHI) scheme and identified factors associated with willingness to join and pay for it; using mixed methodology. The mean age of the respondents was 39.67 with standard deviation of 13.94. Out-of-pocket payment for health care services accounted for 89.5% of healthcare financing. The level of awareness of the state health insurance schemes was 23.1%. The mean satisfaction score with health care system was 2.85 (± 0.51) out of 5 while the mean knowledge score on health insurance concept was 0.32 (± 0.31) out of 1. The average weight of concerns about the scheme management was 2.96 (± 0.47) out of 5. Willingness to join the scheme (which measured the demand for state health insurance scheme) was 65.3% whereas willingness to pay one thousand naira (N1000) per month per individual was 47.1% while willingness to pay four thousand naira (N4000) per month per family was 18.2%. However, preference for family package of health insurance was 73.3%. The maximum amount willing to pay was N1541.45 and N736.99 per month for a family and individual package respectively. Health insurance coverage among respondents was 7.4%. The study included six logistic regression models that identified predictors of satisfaction with present health care system, knowledge of health insurance concept, implementation concerns, willingness to join SHI, willingness to pay N1000 and N4000 respectively.